Periapical Lesions in Intentionally Modified Teeth in a Skeletal Sample of Enslaved Africans (Lagos, Portugal) - Rufino, A. I. (2017)
Intentional dental modifications are alterations of teeth usually performed as a ritual for aesthetic or identity purposes. However, the execution of the technique is not exempt from risk, and can be related to a higher prevalence of dental pathology, more specifically through the exposure of the dental pulp and consequent periapical inflammation. With the aim of analysing the relationship between intentional dental modifications and periapical inflammation, the current study evaluated 81 skeletons (49 females, 19 males, and 13 individuals of unknown sex) of enslaved Africans from Lagos, Portugal (15th-17th centuries), of which 50 (61.7%) had intentionally modified teeth. In all, 2285 sockets and 2063 teeth were observed. Two hundred and three intentionally modified anterior teeth (27.2%) were identified. The differential diagnosis of periapical lesions was made following Dias and Tayles (1997), Dias et al. (2007), and Hillson (2001). Twenty five individuals (30.9%) and 54 teeth (25 anterior and 29 posterior) showed macroscopic evidences of periapical lesions. In the anterior dentition, intentional modification was identified as the probable aetiology of 17 (68.0%) periapical lesions, mostly granulomata or cysts, but also abscesses. The association between intentional modifications of the dentition and the presence of periapical lesions was found in both the maxilla and mandible. These results suggest that this cultural practice can predispose teeth to periapical inflammation, which may cause pain and sensitivity to cold, heat, and pressure, and probably had a negative impact on the quality of life of these individuals.